2020
DOI: 10.1002/bies.202000011
|View full text |Cite
|
Sign up to set email alerts
|

Turning a Drug Target into a Drug Candidate: A New Paradigm for Neurological Drug Discovery?

Abstract: The conventional paradigm for developing new treatments for disease mainly involves either the discovery of new drug targets, or finding new, improved drugs for old targets. However, an ion channel found only in invertebrates offers the potential of a completely new paradigm in which an established drug target can be re‐engineered to serve as a new candidate therapeutic agent. The L‐glutamate‐gated chloride channels (GluCls) of invertebrates are absent from vertebrate genomes, offering the opportunity to intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…It is known that the release of glutamate plays an important role in epilepsy (Chen et al 2023a ). Buckingham et al found an inhibitory glutamate receptor in invertebrates, which does not exist in vertebrates (Buckingham et al 2020 ). Modifying this exogenous receptor and introducing it into the human body can serve as a tool for studying neural circuits, achieving targeted therapy for epilepsy.…”
Section: Drug Therapy Targeting Neural Circuits In Epilepsymentioning
confidence: 99%
“…It is known that the release of glutamate plays an important role in epilepsy (Chen et al 2023a ). Buckingham et al found an inhibitory glutamate receptor in invertebrates, which does not exist in vertebrates (Buckingham et al 2020 ). Modifying this exogenous receptor and introducing it into the human body can serve as a tool for studying neural circuits, achieving targeted therapy for epilepsy.…”
Section: Drug Therapy Targeting Neural Circuits In Epilepsymentioning
confidence: 99%
“…Because the glutamate-gated chloride channels of invertebrates are absent from vertebrate genomes, it has been suggested to introduce this exogenous, inhibitory, L-glutamate receptor into vertebrate neuronal circuits either as a tool to study neural networks or as a treatment for epilepsy. 21,69 Dimitri Kullmann and colleagues mutated a glutamate-gated chloride channel to impart an increased L-glutamate sensitivity and expressed it in excitatory neurons of rats, using a chemogenetic approach. 70 This exerted an antiseizure effect in the pilocarpine and tetanus toxin seizure models in rats.…”
Section: Mechanisms Of Action Of Ivermectinmentioning
confidence: 99%
“…Several mechanisms of action are considered for IVM. The primary mechanism of action is related to the glutamate-gated chloride channels [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%